The impact of a school backpack's weight, which is carried on the back of a 7-year-old students of both sexes, on the features of body posture in the frontal plane - Mirosław Mrozkowiak; Marta Stępień-Słodkowska (BMC, 2022)
Abstract Background The lifestyle of children has a significant impact on the future health of the whole society. Therefore, health education, prevention and monitoring of health determinants is important at every stage of ontogenesis. This requires a thorough knowledge of the schoolchild's environment, perceived as a wide set of stressors, including not only genetic but also epigenetic factors. One of them is the issue of the correct and abnormal body posture at school and on the way there. The goal of the study was to show the influence of the weight of the back carried container with school supplies on body posture. Method The research was carried out as part of a project that examined the impact of carrying weights, which are school supplies, by children on their posture. The research material consisted of data obtained from a group of 65 students (35 girls, 30 boys) aged 7 years. Body posture tests were carried out, using the projection moiré method in 4 positions: 1-habitual posture, 2-posture after 10-min of asymmetric axial load, 3-a posture after 1 min of the load removal, 4-a posture after two minutes of the load removal. Physical fitness was measured with the Sekita test. The obtained data were statistically analyzed. Results The significance of differences between the 1st and 2nd measurements was analyzed to determine the impact of the backpack load and the correlation with physical fitness, and to study its influence on the value of the differences in posture features. Considering the differences in the volume of posture features among boys between the 1st and 2nd measurement, the Wilcoxon's rank test showed a statistically significant difference in the range of all analyzed variables, except for the torso bend angle to the right (KNT+), where no statistically significant change was noted. A statistically significant difference in the volume of all analyzed variables was observed among the girls. Conclusions Carrying school supplies on the back induces significant changes in the value of the features describing the body posture in the frontal plane. The greater weight of the container and carrying time, and intensity of physical effort is the greater the changes will be. Physical fitness has a various and sex-dependent influence on the value of changes in body posture features because of carrying school supplies. Among boys it significantly affects the asymmetry of the torso bend, shoulder height, the waist triangles height and width, whereas among girls it affects the asymmetry of the shoulders and the distance of the angles of the lower shoulder blades from the line of the spinous processes of the spine. Among boys the changes in the value of posture features are mostly influenced by endurance and speed, but strength, power and agility are of lower influence, whereas among girls only agility matters.